AVALIAÇÃO TEMPORAL DA QUALIDADE DE ÁGUA AO LONGO DE UM TRECHO DO ARROIO DA RONDA EM PONTA GROSSA – PARANÁ - SIMONELI, GUSTAVO FORASTIERE (2018)
The Ronda River, located in Ponta Grossa – Parana, is exposed to anthropic activities such as urban occupations near the banks, absence of riparian vegetation, impermeable areas soil, construction waste, a sewage treatment plant, among others that may influence the characteristics of water. And during the monitored period effluents discharges wered observed by rainwater gallery and clandestine connections in the water body that began in march 2017. Therefore, this research aimed to verify the water quality from the water body during the period of October 2016 to September 2017 from the combined use of water quality parameters analysis, water quality indexes and adjacent area observations. Were determined six sampling points that presented different characteristics along the water body. Was used the WQI of Environmental Company of Sao Paulo, the WQI created by the Canadian Council of Ministers of the Environment and the Complex Pollution Index. The results showed that concentrations of E. coli and total-P in nonconformity with classes 2 and 3, both from the stream, of CONAMA nº 357 durint the spring and summer. In the autumn, other parameters showed in nonconformit, such as E. coli, total-P, biochemichal oxygen demand and oxygen dissolved. This increase in registered pollutants from autumn occurred due to the occasional discharge of untreated domestic effluent upstream of the second sampling point. . The point near upstream presented good water quality, being classified in all water quality parameters as the less polluted. Whereas the place with higher pollution level, downstream of ETE Ronda and with agricultural activities around. It was verified that before the discharges the water body presented, in most of its course, concentrations of total-P and E. coli in nonconformity with classes 2 and 3 of CONAMA nº 357 (BRASIL, 2005). Probably, agricultural activities, urban occupations around, impermeable areas, absence of riparian vegetation and discharges from ETE Ronda influenced the high concentration of nutrients and pathogenic microorganisms, due the absence of anthropogenic activities. . The water quality indexes indicated this place as the worst water body condition along the river course. With the exception of the first sampling point, there was an increase in pollution levels in other places after the start of untreated effluent discharges upstream of the second sampling point.